Slow rewarming improves jugular venous oxygen saturation during rewarming - Kawahara, F.; Kadoi, Y.; Saito, S.; Goto, F.; Fujita, N. (Acta anaesthesiologica Scandinavica, 2003)
Background: There have been many studies regarding the etiology of postoperative cognitive dysfunction after coronary artery bypass graft (CABG) surgery. Although its etiology remains unresolved, one possible factor related to postoperative cognitive dysfunction is a reduced internal jugular venous oxygen hemoglobin saturation (SjvO2) during the rewarming period. The purpose of this study was to examine the effect of rewarming rates on SjvO2 during rewarming. Methods: One‐hundred patients scheduled for elective CABG surgery were randomly divided into two groups; control group (0.48 ± 0.09°C, n = 50), slow rewarming group (0.24 ± 0.09°C, n = 50). After the induction of anesthesia, a fiberoptic oximetry oxygen saturation catheter was inserted into the right jugular bulb to monitor SjvO2 continuously. Hemodynamic parameters, arterial and jugular venous blood gases were measured at nine time‐points. Results: Cerebral desaturation (defined as a SjvO2 value below 50%) during rewarming was more frequent in the control group than in the slow group. Cerebral desaturation time (duration when SjvO2 was less than 50%) and the ratio of the cerebral desaturation time to the total CPB time in the control group differed significantly from those in the slow group (control group: 17 ± 11 min, 12 ± 4%, slow group: 10 ± 8 min, 7 ± 4%, respectively, P < 0.05). There was no significant difference in mini‐mental state examination on the day before the operation nor at 1 month after the surgery among four values (the day before the operation: control group; 48 ± 8, slow group; 48 ± 7, at one month after the surgery: control group; 46 ± 7, slow group; 45 ± 9). Conclusions: A slow rewarming rate could reduce the chance of a decrease in SjvO2 during rewarming.